Die NG Kerkorde – 1962: Die Dordtse Kerkorde aangepas by die eise van die dag? - Strauss, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
The Church Order of the Dutch Reformed Church in 1962: The Church Order of Dordt adapted to the demands of the time? A thorough church historical investigation of the validity of this title with the question mark omitted, proofs the correctness of it. Through its history the Dutch Reformed Church (DRC) maintained an affinity for the Church Order of Dordt (DCO). Some of the typical principles of the DCO are also visible in the first church order of the General Synod of the DRC in 1962. It must be said, however, that in some instances DRC-customs spoke louder than the demands of the principles of Dordt or of the time. The influence of Dordt through the order of the Reformed Churches of the Netherlands which, as a modern replica of the DCO, was used as a basis for the new order of the DRC in 1962, is visible in every section of the latter.